DWP’s Registration And Population Interaction Database (RAPID) – what is it and why researchers will want it - Knox, Graham; Needham, Andrew (International Journal of Population Data Science, 2025)
Objectives We will deliver an overview of the Registration And Population Interaction Database (RAPID) and give people the opportunity to see the potential it has to offer for research in advance of it being available in the ONS SRS/IDS. Methods RAPID has been developed by DWP to utilise existing data extracts and bringing selected information together into a coherent view of what citizens who interact with DWP, HMRC or Local Authorities (via Housing Benefit) systems are doing during the tax year. This data provides a valuable asset in understanding the journeys and interactions between employment, self employment and benefit accrual and receipt. This data will allow for insights into the UK economy, labour force trends, impacts of the cost of living crisis and any future accrued benefit liabilities as well as helping answer numerous Evidence Strategy questions. Results We will present some analyses created using RAPID to demonstrate what is possible, including: Income analysis by, for example age, gender, region and tax year. Self-employment rates Employment rates by age by local authority over time Universal Credit, Conditionality and Health Journeys Personal Independence Payments by payment rates Carers Allowance – qualifying benefit and relationships Customer journeys in and out of employment and different benefit receipt Conclusion As use of RAPID increases, we want to be able to take on board user feedback in terms of being able to further develop RAPID, to be able to provide means of support for its use and what resources we develop. This session will be a step towards that journey.